2020
DOI: 10.3390/pharmaceutics12111125
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Ultrasound Contrast Agents for Blood-Brain Barrier Opening with Focused Ultrasound

Abstract: The blood-brain barrier is the primary obstacle to efficient intracerebral drug delivery. Focused ultrasound, in conjunction with microbubbles, is a targeted and non-invasive way to disrupt the blood-brain barrier. Many commercially available ultrasound contrast agents and agents specifically designed for therapeutic purposes have been investigated in ultrasound-mediated blood-brain barrier opening studies. The new generation of sono-sensitive agents, such as liquid-core droplets, can also potentially disrupt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 165 publications
1
35
0
Order By: Relevance
“…Currently available studies have suggested that multiple ultrasound parameters including acoustic pressure, pulse length, frequency of the transducer, and pulse repetition frequency have shown to affect the reversibility of BBB permeability (Baseri et al, 2010 ; Leinenga et al, 2016 ; Snipstad et al, 2018 ). After setting the proper ultrasound parameters, repeated opening of the BBB is safe without causing overt damage according to the experimental findings from larger animals (McDannold et al, 2007 ; Dauba et al, 2020 ). However, it still remains uncertain whether long-term BBB opening is associated with a certain degree of tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently available studies have suggested that multiple ultrasound parameters including acoustic pressure, pulse length, frequency of the transducer, and pulse repetition frequency have shown to affect the reversibility of BBB permeability (Baseri et al, 2010 ; Leinenga et al, 2016 ; Snipstad et al, 2018 ). After setting the proper ultrasound parameters, repeated opening of the BBB is safe without causing overt damage according to the experimental findings from larger animals (McDannold et al, 2007 ; Dauba et al, 2020 ). However, it still remains uncertain whether long-term BBB opening is associated with a certain degree of tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the methods mentioned above, a physical BBB opening technique with ultrasound has aroused broad attention from researchers worldwide and has been extensively discussed in the literature in recent decades (Liu et al, 2010a , b ). Nowadays, substantial evidence has demonstrated that focused ultrasound (FUS) coupled with microbubbles (1–10 μm in diameter) could lead to transient, focal, and reproducible BBB opening, thus enabling the therapeutic agents/genes across the BBB without long-term deficits in barrier function (Hernot and Klibanov, 2008 ; Sheikov et al, 2008 ; Dauba et al, 2020 ). The safety of ultrasound-induced BBB opening has been validated with magnetic resonance imaging (MRI) and histology results in a number of rodent models (Hynynen et al, 2001 ; Kinoshita et al, 2006 ; Leinenga et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…FUS offers unique perspectives to induce safe, reproducible and localized BBB disruption in vivo [20]. Interestingly, mapping of [ 18 F]FDS brain distribution within the sonicated area displayed a gradient from the center to the periphery (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, numerous studies have proposed promising strategies to improve the delivery of therapeutic agents to the brain by circumventing or overcoming the BBB during the last decades. These strategies include intracerebroventricular injections (Lopachev et al, 2019), convection enhanced delivery (Zhan and Wang, 2018), inhibition of efflux transporters (Sanchez-Covarrubias et al, 2014), chemical modification (Al-Ahmady, 2018), and the application of hyperosmotic agents (Patel et al, 2009) or focused ultrasound (Dauba et al, 2020;Lin et al, 2020;Wu et al, 2021a), and so on. However, the limitation of these administration routes is marred by safety concerns, invasive, and erratic efficacy.…”
Section: Introductionmentioning
confidence: 99%